A Typology of Employees' Responses to Participative Work Systems - Silva, M. Gabriela (XXIV Jornadas Luso-Espanholas de Gestão Científica, 2014)
The debate about the strengths and weaknesses of teamwork fails to address adequately the question of employees’ perceptions on work reforms. Drawing on previous studies available in the literature (Boon et al., 2009; Kristensen & Lotz, 2011), the author seeks to overcome this limitation by developing a fourfold typology of team members’ response to teamwork. The aim is to advance theoretical understanding about the action orientations that employees adopt when confronting the reorganization of their jobs.